(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2023)
This book review critiques the Book Paremiologia: enfoques interdisciplinares, which is a collaborative project organized by Andrea Garcia Muniz, Maria Lalicata and Thyago José da Cruz, housed under the Federal University of Mato Grosso do Sul in Brazil. The importance of understanding designation of linguistic terminology is highly debated, calling readers to the awareness of appropriate language use for effective communication. Historical contexts of proverbs together with their cultural nuances are dissected through the contrastive analyses of proverbs and sayings in Portuguese, Spanish, Italian, French, Ancient Greek and other European languages. The main arguments underscored in this collaborative work divided into ten chapters reveal how paremias are a pertinent resource in the study of languages and the understanding of cultural spaces.